Development of the visual white matter pathways mediates development of electrophysiological responses in visual cortex. Issue 17 (6th September 2021) - Caffarra, Sendy; Joo, Sung Jun; Bloom, David; Kruper, John; Rokem, Ariel; Yeatman, Jason D.
Abstract: The latency of neural responses in the visual cortex changes systematically across the lifespan. Here, we test the hypothesis that development of visual white matter pathways mediates maturational changes in the latency of visual signals. Thirty‐eight children participated in a cross‐sectional study including diffusion magnetic resonance imaging (MRI) and magnetoencephalography (MEG) sessions. During the MEG acquisition, participants performed a lexical decision and a fixation task on words presented at varying levels of contrast and noise. For all stimuli and tasks, early evoked fields were observed around 100 ms after stimulus onset (M100), with slower and lower amplitude responses for low as compared to high contrast stimuli. The optic radiations and optic tracts were identified in each individual's brain based on diffusion MRI tractography. The diffusion properties of the optic radiations predicted M100 responses, especially for high contrast stimuli. Higher optic radiation fractional anisotropy (FA) values were associated with faster and larger M100 responses. Over this developmental window, the M100 responses to high contrast stimuli became faster with age and the optic radiation FA mediated this effect. These findings suggest that the maturation of the optic radiations over childhood accounts for individual variations observed in the developmental trajectory of visual cortex responses. Abstract : This study elucidates the relationship between structural and functional properties of the visual pathways and how they change during childhood. Developmental changes of visual white matter pathways account for latency variations in electrophysiological responses of visual cortex. The present findings are an example of how relating white matter properties to functional aspects of the brain can help us reach a more complete understanding of the link between development of brain connectivity and changes in electrophysiology.